Canadian perioperative nurses’ engagement and perceptions of continuing professional development - Ahlquist, Eli (Operating Room Nurses Association of Canada Journal, 2024)
Professional competence achieved through continuing professional development (CPD) is considered essential to nursing because of its impacts on quality of care and safety. Engagement in these activities contribute to a nurse’s practice through resultant improvements in their knowledge, skills, and confidence. They also contribute to enhanced professional status and relationships with other healthcare practitioners. However, there are structural barriers that impede participation as well as an unacceptable impact from lateral violence. This research utilized a mixed methods online survey to explore the engagement and perceptions of Canadian perioperative registered nurses regarding CPD. The findings of this study suggest that perioperative nurses engage in regular CPD activities as part of their professional practice. The preferred activities as rated by participants were: Self-directed learning activities; In-services; and Formal continuing education. The findings of this research are significant to perioperative nursing because they highlight the activities that nurses perceive to be the greatest value, as well as confirming the presence of barriers present in the literature. Consequently, this information can be used to develop and implement strategies that will enhance CPD, thereby improving perioperative nursing practice.